Development of Discovery Learning-Based E-LKPD to Enhance Students' Learning Motivation and Achieve Critical Thinking Skills in Salt Hydrolysis Material - Hayyun; Ibnu haldun; Sri Winarni (Postgraduate, University of Mataram, 2024)
This study aims to evaluate the viability, practicality, and effectiveness of based on discovery learning (E-LKPD) in raising students' motivation to learn and cultivating their critical thinking abilities (CTS). This study adopts a quantitative methodology by utilizing the research and development (R&D) technique and the Borg and Gall model. Sixty-two students from SMA Negeri 1 Baitussalam's class XI make up the study sample. The average results of the viability test for the E-LKPD, reviewed from the aspects of material completeness, accuracy, currency, and alignment with objectives, obtained a percentage of 91.25% with the criterion of